Bahasa Indonesia LATIHAN SENAM YOGA TERHADAP PENURUNAN DISMENORE REMAJA PUTRI DI SMA BANDUNG - Mulya, Adelse Prima; Lukman, Mamat; Yani, Desy Indra (E-Jurnal Medika Udayana; Vol 11 No 11 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i11.P09, 2022)
Dysmenorrhea is an unpleasant experience in women, especially those who experience menstruation. Conditions experienced by women during dysmenorrhea can be either primary or secondary so that it can interfere with daily activities and school. Dysmenorrhea disturbs nearly 50% of women of reproductive age and 60-85% in their teens. One of the non-pharmacological therapies that can be done to reduce this dysmenorrhea is yoga exercises. The purpose of this study was to determine the effect of yoga exercises in reducing dysmenorrhea pain in female students at one of the high schools in Bandung. This research design uses Quasi Experiment one group (one group pre-test - post test design). Sampling was done by purposive sampling. The sample in this study amounted to 32 people and died before the implementation of the posttest as many as 23 samples so that the remaining 9 samples. Samples were given yoga exercises three times a week for 30 minutes. Analyzing data using Wilcoxon test with 95% confidence level. Wilcoxon test results obtained p = 0.003. This shows that yoga exercises are quite effective in reducing the pain threshold of dysmenorrhea in Bandung City High School students. It is hoped that the school will inform this activity to all students and can be carried out at home by students as an effort to reduce dysmenorrhea.